Uveal melanoma incidence trends in Canada: 1992–2010 vs. 2011–2017 - Conte, Santina; Lagacé, François; Ghazawi, Feras M.; Cattelan, Leila; Nath, Siddharth; Dhillon, Jobanpreet; Nedjar, Hacene; Rahme, Elham; Sasseville, Denis; Burnier, Miguel N.; Litvinov, Ivan V. (Frontiers in Medicine, 2023)
Background/aims Uveal melanoma is the most common type of non-cutaneous melanoma and the most common ocular malignancy in the adult population, especially affecting Caucasians (98% of cases). Despite its low incidence rate, we have noted increasing incidence trends in recent years. Methods We analyzed uveal melanoma incidence data using the Canadian Cancer Registry (CCR) for 2011–2017 years. The data was examined using the International Classification of Diseases for Oncology, Third Edition, codes for all uveal melanoma subtypes. The data for 2011–2017 was then compared to previously published work by our research group for uveal melanoma incidence in Canada between 1992 and 2010 using the same methodology. Results Between 2011 and 2017, 1,215 patients were diagnosed with uveal melanoma, 49% of whom were females. The percentage distribution of uveal melanoma between the sexes was similar between 1992–2010 and 2011–2017, whereby of the 2,215 diagnoses of uveal melanoma in 1992–2010, 47.9% were females. The change in the incidence rate for this cancer has doubled between 1992–2010 and 2011–2017, from 0.074 to 0.15 cases per million individuals per year. Our study documents that the Canadian 2011–2017 age-standardized incidence rate (ASIR) for uveal melanoma against the World Health Organization (WHO) 2000–2025 world population standard was 5.09 cases per million individuals per year (95% confidence interval, 4.73–5.44), as compared with the 1992–2010 rate of 3.34 cases per million individuals per year (95% confidence interval, CI 3.20 to 3.47). Conclusion This work demonstrates an ongoing, steady increase in uveal melanoma incidence in Canada in recent years.